New Lives Given by Cell Death: Macrophage Differentiation Following Their Encounter with Apoptotic Leukocytes during the Resolution of Inflammation - Ariel, Amiram; Serhan, Charles N. (Frontiers in Immunology, 2012)
Monocytes that migrate into tissues during inflammatory episodes and differentiate to macrophages were classified earlier as simply two broad phenotypes: classically (M1)- or alternatively (M2)-activated macrophages, based on their exposure to different fate-determining mediators. These macrophage subsets display distinct molecular markers and differential functions. At the same time, studies from recent years found that the encounter of apoptotic leukocytes with macrophages leads to the clearance of this cellular "debris" by the macrophages, while concomitantly reprogramming/immune-silencing the macrophages to an M2-like phenotype. In this manuscript we review the recent information regarding the impact of apoptotic cells on macrophage phenotype changes in molecular terms. We will focus on recent evidence for the in vivo existence of distinct pro-resolving macrophages and the role of apoptotic cells, specialized lipid mediators, and glucocorticoids in their generation. Consequently, we will suggest that these pro-resolving CD11blow macrophages have metamorphed from M2-like macrophages, and modulated their protein profile to accommodate the changes in their function.